Paramotor Trike Design and Analysis - Selvam, Aravind; Omar, Zamri (Progress in Aerospace and Aviation Technology, 2023)
A paramotor trike refers to an ultralight aircraft that is attached to a paraglider. A trike with a rear-mounted engine provides thrust force, enabling the vehicle to take off. The main objective of this study is to develop the modelling simulation of a two-seater paramotor trike and analyze the stresses acting on the frame structure of the paramotor trike through static and drop test simulations. In this study, the paramotor trike conceptual design is developed using SolidWorks. The safety factor for the static test and drop test is satisfactory based on the deformation, strain, and stress results. Moreover, the paramotor trike that was developed achieved its lightweight goal of 99 kg with an ergonomic design and has a maximum takeoff weight of 246 kg.